Inovasi Program Bank Sampah Melalui Pembangunan Komunitas Masyarakat: Berdasarkan Pengalaman Kelurahan Bahagia - Pramudya, Pramudya; Kurniansyah, Dadan; Rizki, Mochammad Faizal (Universitas Muhammadiyah Sumatera Utara, 2024)
Slum settlements in urban areas are a problem that is often faced by a number of big cities in Indonesia. One of the minimum provision of facilities and infrastructure is related to waste management. Based on the 2020 National Waste Management Information System (SIPSN), West Java is the 3rd largest nationally in terms of contributing to landfill, namely 4,143,000 tons/year. Bekasi Regency is the largest in West Java, with managed waste of 40.97%. Based on the Central Bureau of Statistics for Bekasi Regency in 2017, 1,500 tons of waste came from household/domestic waste. In 2010 the community of the Happy Waste Bank Association (PBSB) was established with an innovative waste bank program. The research method used is descriptive qualitative. This research is based on the innovation development theory of Dr. Khairul Muluk which includes three stages, namely the development of innovation leadership, community development, and innovation performance development. The results of this study indicate that the development of innovation is in accordance with the three stages based on Dr. Khairul Muluk. The waste bank program is still running today, but its implementation is still not optimal, there are obstacles such as scavengers who pick up waste that has been sorted by residents (waste bank customers), as well as price fixing by collectors. Therefore further monitoring and review is needed on the prices of organic waste so that the waste bank program runs well.Keywords: Happy Village, Innovation Development, Waste Bank